2018
DOI: 10.1007/s00281-018-0718-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex and sex steroids impact influenza pathogenesis across the life course

Abstract: Males and females differ in the outcome of influenza A virus (IAV) infections, which depends significantly on age. During a typical seasonal influenza epidemic, young children (<5 years of age) and aged adults (65+ years of age) are at greatest risk for severe disease, and among these age groups, males tend to suffer a worse outcome from IAV infection than females. Following infection with either pandemic or outbreak strains of IAVs, females of reproductive ages (i.e., 15-49 years of age) experience a worse ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…48 Conversely, several reports claimed that the male testosterone was associated with higher sensitivity to influenza infection in wild-type mice. [49][50][51] These observations are consistent with studies by Sutherland et al showing that androgen blockade in mice and humans supports thymic regeneration, 52 which in turn enhances HIS reconstitution following HSC transplantation. 53 However, studies by Nowak et al suggested that different fractions of the androgen hormones in humans afflicted by IAV infections are modulatory, rather than implicitly immunosuppressive.…”
Section: Discussionsupporting
confidence: 89%
“…48 Conversely, several reports claimed that the male testosterone was associated with higher sensitivity to influenza infection in wild-type mice. [49][50][51] These observations are consistent with studies by Sutherland et al showing that androgen blockade in mice and humans supports thymic regeneration, 52 which in turn enhances HIS reconstitution following HSC transplantation. 53 However, studies by Nowak et al suggested that different fractions of the androgen hormones in humans afflicted by IAV infections are modulatory, rather than implicitly immunosuppressive.…”
Section: Discussionsupporting
confidence: 89%
“…The severity of COVID-19 symptoms shows clear sex differences with more severe cases and higher mortality reported in men than women [9]. Similar sex differences were revealed in the outcome of influenza A virus infections probably mediated by the impact of sex steroid hormones in immune responses [21]. Although the studied population was not sex-balanced (1592 women vs 902 men) our analyses stratified by sex also revealed potential sex differences in the effects of several immunomodulatory compounds.…”
Section: Discussionsupporting
confidence: 63%
“…Given the wide variations in human versus rodents in vitro versus in vivo systems, epidemiological studies have shown that there is not a universal paradigm regarding the role of gender or sex hormones on the immune response to respiratory viruses. It is hypothesized that the disease outcomes are ultimately a combination of the magnitude of the immune response and degree of host tissue damage ( 92 , 93 ). There is a male bias when a weaker immune response contributes to damage, while a female bias may occur due to a stronger immune response that causes damage.…”
Section: Immune Responsementioning
confidence: 99%